Exposure to Traffic-Related Particulate Matter and Prevalence of Respiratory Symptoms among Commercial Drivers in Abuja, Nigeria - Clement Awe; Abimbola Thomas; Samuel Bankole; Adetoun Olaitan (Work and Health, 2026)
Background: Traffic-related air pollution poses a significant occupational health risk, particularly for commercial drivers in rapidly urbanizing cities. This study assessed exposure to fine particulate matter (PM2.5) and its association with self-reported respiratory symptoms among commercial drivers in Abuja, Nigeria. Methods: A cross-sectional study was conducted among 400 commercial drivers from two local government areas. Ambient PM2.5 concentrations were measured using a calibrated Bosean portable dust detector at four motor parks over four weeks. Respiratory health data were collected using the American Thoracic Society Respiratory disease questionnaire (ATS-DLD-78) administered by interviewers. Logistic regression was used to explore associations between PM2.5 and respiratory symptoms. Results: 24-h mean PM2.5 concentrations ranged from 53.6 to 76.2 μg/m3, exceeding WHO guideline limits at all sites. Prevalent respiratory symptoms included cough 81.0%, (95% CI: 77.0–84.5), phlegm production 68.4% (95% CI: 45.5–55), runny/blocked nose 70.8% (95% CI: 66.0–75.3), wheezing 19.5% (95% CI: 15.8–23.8) and breathing difficulty 21.8% (95% CI: 17.8–26.0). Higher PM2.5 exposure was significantly associated with increased odds of doctor-diagnosed asthma (AOR = 13.2; 95% CI: 6. 9–25.4; p < 0.001), although this exploratory finding warrants further investigation using more robust exposure assessment and longitudinal study designs. Driving experience, daily work hours, age, and income were also significant predictors of respiratory symptoms. Conclusion: Commercial drivers in Abuja are exposed to PM2.5 concentrations substantially exceeding WHO guidelines, with a high burden of associated respiratory morbidity. Targeted occupational health interventions, strengthened emission regulations, and improved road infrastructure are needed. Further, there is need to safeguard public health in Nigeria through regulatory standards that aligns with latest scientific evidence on PM2.5.